Rasionalitas Masyarakat dalam Memilih Calon Kepala Desa Nomor Satu pada Pilkades 2019 di Desa Mojongapit - Dinda Mirtanty; Agus Machfud Fauz (Jurnal ISIP: Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
This research was motivated by the victory of the number one village head candidate in the 2019 Pilkades in Mojongapit Village who worked as a trader, did not have a political background, and did not hold a bachelor’s status. The candidate election for the village head was due to the community’s objectives (action rationality). With this phenomenon, this study aims to find out the rationality of the people of Mojongapit Village in choosing a candidate for a village head in the 2019 Pilkades. This study uses a qualitative method with the Verstehen approach, which aims to interpret every action taken by the community, such as choosing a candidate for a village head. In addition, the research will analyze reality using the perspective of Max Weber’s phenomenological theory, which focuses on the rationality of action. The study results show that the community’s reasonable measures in choosing the number one candidate for village head include: First, instrumental actions: vision and mission according to community expectations and ease of administration. Second, effective measures: disappointment in previous leadership, admiration for authority, sympathy caused by physical appearance and character. Third, value-oriented action: the candidate for the village head has been active in the Nahdlatul Ulama student association. Fourth, traditional acts of family background are within the same neighbourhood’s scope. The conclusion of this study shows that the community chooses the village head based on rationality